2020
DOI: 10.1101/2020.04.10.036053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STAT1 dissociates adipose tissue inflammation from insulin sensitivity in obesity

Abstract: 25Obesity fosters low-grade inflammation in white adipose tissue (WAT) that may contribute 26 to the insulin resistance that characterizes type 2 diabetes mellitus (T2DM). However, the 27 Research). cDNA was synthesized using SuperScript VILO Master Mix (Thermo Fisher). 132

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Obesity often causes chronic inflammation, and related studies have revealed that obesity, low-intensity chronic inflammation, and insulin resistance are closely associated with each other [29,30]. Adipose tissues release various adipokines involved in energy homeostasis that interact with macrophages and play a crucial role in the inflammatory response in adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity often causes chronic inflammation, and related studies have revealed that obesity, low-intensity chronic inflammation, and insulin resistance are closely associated with each other [29,30]. Adipose tissues release various adipokines involved in energy homeostasis that interact with macrophages and play a crucial role in the inflammatory response in adipose tissues.…”
Section: Discussionmentioning
confidence: 99%